1995
DOI: 10.1007/bf02634566
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of a cell line derived from embryos of the potato tuber mothPhthorimaea operculella (Zeller)

Abstract: A cell line from the main insect pest of potatoes in tropical and subtropical areas, Phthorimaea operculella (Zeller), was obtained from embryoculture. These cells were cultured in Grace's modified medium. The cell line, designated ORS-Pop-93, had a heterogeneous population consisting of spherical and spindle cells with great capacity to adhere and a doubling time of 40 h. They were subcultured for more than 60 passages. Their polypeptidic profile was different from profiles of other lepidopteran cell lines. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…After the 5 'h passage, only rounded cells of varied sizes were observed. The morphology of the ORS-Pop-95 cell line is similar to the cell lines previously established at 27 ° C 03, 15,20). Increasing the temperature to 27 ° C does not affect the morphology of the eells established at 1W C. Winstanley and Crook (29) observed that a cell line established from embryos of Cydia pomonella at 19 ° C changed morphology when euhivated at 27 ° C. Thus, they deeided to select different cultures to obtain more homogeneous cell lines.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…After the 5 'h passage, only rounded cells of varied sizes were observed. The morphology of the ORS-Pop-95 cell line is similar to the cell lines previously established at 27 ° C 03, 15,20). Increasing the temperature to 27 ° C does not affect the morphology of the eells established at 1W C. Winstanley and Crook (29) observed that a cell line established from embryos of Cydia pomonella at 19 ° C changed morphology when euhivated at 27 ° C. Thus, they deeided to select different cultures to obtain more homogeneous cell lines.…”
Section: Discussionmentioning
confidence: 88%
“…The ORS-Pop-93 cell line, consisting of heterogeneous cell types (15) and five other cell lines with homogeneous cell types, obtained by selecting (Pop2, Pop3 and Pop4) or cloning (cllA and cl2B) from embryonic cells of P. operculella (13), were cultivated in modified Grocers medium (14) containing 10% fetal bovine serum (FBS) at 27 ° C. The cells were routinely subcultured every 5 to 7 d and seeded with 1 to 2 × 10 ° cells in 25-cm 2 flasks.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations